Rukhsah dalam Salat Berdasarkan Naskah Naẓam Rukhṣiyah Karya Kiai Haji Ahmad Rifa’i: Suntingan Teks Disertai Kajian Pragmatik - Nur Robiah; Nur Fauzan Ahmad (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2026)
Naẓam Rukhṣiyah manuscript is one of the manuscripts written in Javanese using Pegon script. This text contains teachings on rukhsah (legal concessions) in Islamic prayer, particularly qashar (shortened prayer) for travelers and jamak (combined prayer) for the ill. This research aims to present an edited version and translation of the text, as well as to explain its content, specifically the conditions under which a Muslim with a legitimate ‘uzur syar’i (legal excuse) is permitted to perform jamak and qashar prayers. The theories used in this research are philology and pragmatics. The methodology is divided into three parts: data collection, data analysis, and presentation of the analysis results. In the data collection phase, the researcher conducted both field studies and literature reviews. In the data analysis phase, philological theory was applied to present the edited version and translation of the text, while pragmatic theory was used to analyze the teachings within the Naẓam Rukhṣiyah related to rukhsah in jamak and qashar prayers. During the editing process, several philological phenomena were found and noted in the critical apparatus, including lacunae, dittography, additions, and substitutions. The results of this study provide a critical edition of the text aimed at minimizing errors in writing or copying, along with a translation from Javanese into Indonesian. The teachings found in the Naẓam Rukhṣiyah text include; (1) qashar and jamak prayers; (2) Conditions under which qashar is permitted; (3) Conditions for performing jamak taqdim and jamak ta’khir; (4) Combined prayer for those who are ill.